Significados da secularização e lugar das religiões na esfera pública na perspectiva da cidadania complexa - Decothé Junior, Joel Francisco (Universidade do Vale do Rio dos Sinos, 2022)
The debate about the meaning of secularization and the place of religions in the modern public sphere is the central objective of this investigation. For this, I initially reconstituted the elucidative theoretical elements about the subject from the theories of Jürgen Habermas and Charles Taylor. From this, I took as contribution for the justification of my evaluation and position in this debate the notion of complex citizenship contributed by Adela Cortina as a complementary interpretation with the position of the philosophers mentioned above in the main philosophical discussion. In this context, the question that moves my argumentation in this research is the following: which are the meanings of the secularization and the place of religions in the modern public sphere at the light of Habermas, Taylor and Cortina? For this, in the first moment, I sought to rebuild some general constitutive premises about the meanings of secularization and the place of religions in the public sphere within the scope of the cultural secular tradition in the westerly modernity. Then, I introduced the analysis of Habermas position about the constellation and the place of religions in the modern post-secular sphere. After this, I rebuild the argument about the meaning of living in a secular era and the place of religions in the public sphere, according to Taylor. In sequence, I seek to comprehend Cortina’s positions about its conception of secular society and the place of religions in the public sphere inside the conceptual standard of complex citizenship. Lastly, I mainly study the ethical implications about the place of religions in the (post) secular public modern sphere, relating the nuances of Habermas position as the translation of the potential semantic content of the religious languages to the secular language models. I seek forward to understand Taylor’s position about plenitude as a designative meaning of life in a secular era. And, lastly, I explain the position which I associate myself conceptually in this debate, that is the proposal of civil ethics in the face of the religious sources, having as a foundation the perspective of complex citizenship as a conception with the objective of defending that this notion presents itself as the most adequate way, currently, of interpreting the challenges of the ways of constitution of complex citizen life, coexisting between religious and secular agents against the conflicting phenomenon of cultural and moral pluralism in the contemporary democracies of the western secularized modernity.
Keywords: Secularização; Lugar das religiões; Esfera pública; Cidadania complexa; Secularization; Place of religions; Public sphere; Complex citizenship; ACCNPQ::Ciências Humanas::Filosofia